Studies On Nutritional And Anti-Nutritional Composition Of Bambusa Multiplex (Lour.) Raeusch. Ex Schult - BABITHA BHASKARAN; SRINIVAS MURTHY CHILKUNDA; THARA SARASWATHI KUNIGAL JAGADISHCHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Bambusa multiplex, a multipurpose ornamental and commercial bamboo species used for hedges, construction, basketing and as handicraft material. The shoots are edible and consumed in Southeast Asia and in North eastern regions of India. As earlier investigations does not emphasize on finding out the harvesting time, an attempt has been made to find out the harvesting time to obtain quality shoots. The bamboo shoots were harvested on different days (7-30 days after emergence from ground) and analysed for chemical, nutritional and anti-nutritional components. The shoots harvested at various time intervals showed variation in nutritional composition with an overall decrease in protein and increase in dietary fiber and carbohydrate content. All the nutritional elements except calcium showed decreased content with shoot maturity. The optimum harvesting age for B. multiplex shoots were found to be 7- 10 days with high nutritional content and anti-nutritional component, cyanide was found to be completely absent.